Rationale, design and protocol of a cross-sectional study on pregnancy-related cardiovascular diseases in Tanzania (PRECARDT): burden, characterisation and prognostic significance at delivery. Issue 12 (31st December 2021) - Makubi, Abel; Chillo, Pilly; Mutagaywa, Reuben; Balandya, Belinda; Kisenge, Peter; Tarimo, Vincent; Mujuni, Eva; Msaki, Evarist B; Mgaya, Josephine; Kihunrwa, Albert; Janabi, Mohamed; Kwesigabo, Gideon; et al.
Abstract : Introduction: The paucity of data describing cardiovascular disease (CVD) in pregnancy in many parts of Africa including Tanzania has given rise to challenges in proper management by the healthcare providers. This study is set out to (1) determine the prevalence of a range of CVDs during pregnancy in women attending antenatal clinics in Tanzania and (2) determine the impact of these CVDs on maternal and fetal outcomes at delivery. Methods and analysis: This is a cross-sectional study with a prospective component to be conducted in two referral hospitals in Tanzania. Pregnant women aged ≥18 years diagnosed with a CVD during the antenatal period are being identified and extensively characterised by performing clinical assessment, modified WHO staging, electrocardiography, echocardiography and laboratory tests. Patients identified with CVDs (exposed) and a subset without (unexposed) will be followed up to determine maternal and fetal outcomes at delivery. A minimum sample of 1560 will be sufficient to estimate the prevalence of CVDs with a 95% CI of 2.75% to 5.25%. Ethics and dissemination: The study is being conducted in accordance with the Helsinki declaration on studies involving human subjects. Ethical approvals have been obtained from Muhimbili University (reference number DA.282/298/01.C/) and Bugando Medical Centre (reference number CREC/330/2019) Ethics Committees. Informed consent is sought from all potential participants before any interview or investigations are performed. Study findings will be disseminated to the scientific community through different methods. Results will also be communicated to policymakers and to the public, as appropriate.